Dynamic Modeling of Convective Drying of Pineapple Peels: Bioactive, Physical, and Thermal Properties - Raniza de Oliveira Carvalho; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Francislaine Suelia dos Santos; Mailson Gonçalves Gregório; Lumara Tatiely Santos Amadeu; Henrique Valentim Moura; Nailton de Macedo Albuquerque Junior; Fabrícia Santos Andrade; Emily Bezerra Coutinho Cruz; Emerson Zambrano Lara; Josivanda Palmeira Gomes; et al. (Agriculture)
The fruit processing agroindustry generates waste, mainly composed of peels, which are often discarded but can be utilized as ingredients for developing new food products. However, their high perishability requires the application of preservation techniques, such as drying, which not only extends shelf life but also adds value and enables their conversion into flour, expanding their applications. This study evaluated the convective drying of pineapple peels for flour production, analyzing bioactive, physical, and thermal properties. Moisture was reduced by 91%, reaching a hygroscopic equilibrium of 6.84%. The Two-Term model provided the best fit for the data, with an R2 above 0.9997. Effective diffusivity increased with temperature, ranging from 2.83 × 10−10 m2/s to 7.96 × 10−10 m2/s, with an activation energy of 47.90 kJ/mol, as described by the Arrhenius equation. Thermodynamic properties indicated an endothermic, non-spontaneous process, with reductions in enthalpy (45.21; 45.04 kJ/mol) and entropy (−0.2797; −0.2802 kJ/mol·K) and an increase in Gibbs free energy (135.60–141.20 kJ/mol) at higher temperatures. Fresh peels contained high levels of bioactive compounds, such as phenolics (1740.90 mg GAE/100 g d.b.) and tannins (613.42 mg TAE/100 g d.b.), which were best preserved at 70 °C. Drying altered the physical properties of the flour, resulting in higher absolute, apparent and compact densities, lower porosity (75.81%), and a reduced angle of repose (21.22°) suggesting greater material stability. Thermal analysis identified five mass loss events related to the degradation of water, carbohydrates, proteins, and fibers. Differential scanning calorimetry confirmed the thermal stability of the treatments. Thus, the study highlights pineapple peels as a promising raw material for producing nutrient-rich functional flour, with a drying temperature being a crucial factor in preserving bioactive compounds and achieving desirable product characteristics.